PREVENTIVE ROLES OF BIOACTIVE NATURAL COMPOUNDS IN OXIDATIVE AND NITROSATIVE STRESS MEDIATED PATHOPHYSIOLOGY OF DIABETES MELLITUS: natural products preventing diabetes - SATYAPRAKASH BERAIYA; PIR MOHAMMAD ISHFAQ; ZAVED AHMAD; SWATI TRIPATHI; SIDDHARTHA KUMAR MISHRA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Oxidative stress has emerged as one of the targets in several medical conditions and in several types of clinical researches. Growing evidences from research on diverse diseases show that oxidative stress is conjoined with the pathogenesis of diabetes and its complications. This review has examined the role of oxidative stress in the pathogenesis of insulin resistance and beta-cell dysfunction. A vast variety of medicinal plants and products have been utilized for the prevention of diabetes and its related complications. Natural products such as phenolic acids and flavonoids construct one of the most ubiquitous groups of plant phenolics. At present, the effect of dietary phenolics is of extreme concern due to their antioxidant, free radical scavenging, and as quenchers of singlet oxygen formation. Reactive oxygen species (ROS) as well as reactive nitrogen species play either harmful or beneficial roles in biological systems depending on pathophysiological conditions. This review extends on the fundamental aspect of ROS in biological processes and diseases and how natural bioactive compounds of fruits and vegetables regulate their health improving properties. Flavonoids and phenolics acids are the most important groups of secondary metabolites and bioactive compounds in plants. Diverse phytochemical agents have become the backbone in pharmacotherapy of diabetes by virtue of their antioxidant properties along with their other pharmacological actions. Consequently, accession to obstruction the generation of reactive free radicals or abduct the reactive free radical may yield direct and casual approach for the medication of diabetes and its complications.